Analysis Of Work Motivation And Organizational Culture Towards Human Resource Development With Job Satisfaction As An Intervening Variable In Bappeda East Aceh Regency - Cut Liana Meilani; Sri Rahayu; Kholilul Kholik (CV. Doki Course and Training, 2026)
Human resource development (HR) is a strategic factor in improving the performance of public sector organizations, including the Regional Development Planning Agency (BAPPEDA) of East Aceh Regency. However, human resource development cannot be separated from the role of work motivation, organizational culture, and employee job satisfaction levels. This study aims to analyze the influence of work motivation and organizational culture on the development of human resources with job satisfaction as an intervening variable in BAPPEDA East Aceh Regency. This study uses a quantitative approach with a survey method through the distribution of questionnaires to BAPPEDA employees of East Aceh Regency. The data analysis technique used is path analysis with the help of statistical software. The results of the study show that work motivation and organizational culture have a positive and significant effect on human resource development. In addition, work motivation and organizational culture also have a positive and significant effect on job satisfaction. Job satisfaction has been proven to be able to mediate the influence of work motivation and organizational culture on human resource development. These findings indicate that increasing human resource development in BAPPEDA in East Aceh Regency can be achieved through strengthening work motivation, forming a conducive organizational culture, and increasing employee job satisfaction. This research is expected to be a consideration for organizational leaders in formulating more effective and sustainable HR management policies.